(untitled) (Progressive Agriculture, 2015)
The present study was designed to analyze the production, cost, return and profitability of three winter vegetables (brinjal, country bean and cabbage) production of three villages ofNarshingdi District in Bangladesh. To achieve the objectives, data were collected from 60 farmers. The sample farmers were selected through purposive sampling technique.The major findings of the study were: among the winter vegetables, cabbage production was more profitable. Per hectare profitability of growing vegetables from the viewpoints of individual farmers was measured in terms of gross return, gross margin and value addition. Per hectare gross costs of brinjal, country bean and cabbage production were Tk. 241277, Tk. 162337 and Tk. 204152 respectively, and per hectare average yields of brinjal, country bean and cabbage were estimated at 24175 kg/ha 15774 kg/ha, and 24707 kg/ha, respectively. Per hectare gross returns of brinjal, country bean and cabbage were Tk. 483500, Tk. 347028 and Tk. 494140, respectively. Per hectare net returns of brinjal, country bean and cabbage were Tk. 242223, Tk. 184691, and Tk. 289988, respectively. It shows that cost of production per hectare was higher for brinjal than for cabbage and country bean. The study also shows that per hectare yield, gross returns, gross margin, net return and benefit cost ratio of cabbage were higher than those of country bean and brinjal. Therefore, it is clear that cabbage production was most profitable among the three crops. Progress. Agric. 2014. 25: 47-53